Comprehensive characterization of 21-hydroxylase deficiency in a Chinese pediatric cohort: phenotype, steroid profiles and genetics - Chong, Hemeng; Xue, Guocui; Pi, Yalei; Zhang, Yanan; Li, Yuqian; Xing, Yutong; Chen, Baorong; Zhang, Huifeng (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate the clinical, steroid hormones and genetic characteristics of Chinese children with 21-hydroxylase deficiency (21OHD).MethodsThis retrospective study included 115 children with 21OHD. Clinical data, steroid hormone levels, and genetic information were collected for overall and subgroup analyses. Clinical and steroid hormone characteristics were compared across clinical phenotypes and by sex. Within the salt-wasting (SW) group, characteristics were also compared between newborn screening (NBS)-diagnosed and clinically diagnosed patients. The relationship between Prader scores and both clinical phenotype and steroid hormone levels was analyzed, and the genotype-phenotype correlation, variation frequency and CAH-X CH-1 incidence were calculated.ResultsThe cohort comprised 76 (66.09%) SW, 27 (23.48%) simple virilizing (SV), and 12 (10.43%) non-classic (NC) patients. The overall levels of adrenocorticotropic hormone (ACTH), 17-hydroxyprogesterone(17OHP), and progesterone (P) levels were significantly elevated in SW and SV compared to NC patients. Girls with Prader scores ≥1 had higher hormone levels than those with normal external genitalia. Virilization was more severe in SW than SV girls. NBS significantly reduced the diagnostic delay for SW infants. Functional assays and SpliceAI prediction confirmed that a novel splice variant (c.203-1G>A) induces exon 2 skipping. We also report the first instance of cis double mutations (E3del8bp and p.V282L) on a single allele in two brothers. The allele frequency of p.V282L (5.16%) and CAH-X CH-1 incidence (11.32%) were higher than previously reported.ConclusionThis study expands the 21OHD mutational spectrum with two novel findings: a pathogenic splice-site variant (c.203-1G>A) and cis double mutations on a single allele. We demonstrate phenotype-specific differences in virilization and steroid hormones, underscoring the value of Prader scoring. NBS facilitated earlier diagnosis in SW patients, supporting its nationwide implementation in China. Our findings illustrate a distinct genetic architecture for 21OHD in the Chinese population, correlating with increased detection of NC cases.